Design of microstrip bandpass filters with multiorder spurious-mode suppression - CHEN, Chi-Feng; HUANG, Ting-Yi; WU, Ruey-Beei (IEEE transactions on microwave theory and techniques, 2005)
This paper proposes a bandpass filter design method for suppressing spurious responses in the stopband by choosing the constitutive resonators with the same fundamental frequency, but staggered higher order resonant frequencies. The design concept is demonstrated by a four-pole parallel-coupled Chebyshev bandpass filter and a compact four-pole cross-coupled elliptic-type bandpass filter. Each filter is composed of four different stepped-impedance resonators (SIRs) for which a general design guideline has been provided in order to have the same fundamental frequency and different spurious frequencies by proper adjusting the impedance and length ratios of the SIR. Being based on knowledge of the coupling coefficients and following the traditional design procedure, the resultant filter structures are simple and easy to synthesize. The measured results are in good agreement with the simulated predictions, showing that better than -30-dB rejection levels in the stopband up to 5.4f/sub 0/ and 8.2f/sub 0/ are achieved by the Chebyshev and quasi-elliptic filters, respectively.